Analisis Kadar Senyawa Bioaktif dan Aktivitas Antioksidan Beras Hitam (Oryza sativa L. indica) dan Kacang Hijau (Vigna radiata L.) - Imelda Afriana Putri; Any Guntarti; Sapto Yuliani; Nurkhasanah Nurkhasanah (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Excessive free radicals can induce oxidative stress and contribute to the pathogenesis of various degenerative diseases, necessitating the availability of effective antioxidants. Black rice (Oryza sativa L. indica) and mung bean (Vigna radiata L.) are recognized as rich sources of bioactive compounds with prospective antioxidant properties. Objective: This study aimed to analyze the bioactive compound content and antioxidant activity of black rice and mung bean extracts. Methods: Extraction was performed using maceration with 80% ethanol containing 3% citric acid for black rice and 70% ethanol for mung bean. Total anthocyanin and total polyphenol contents were determined in black rice extract, while total polyphenol and total flavonoid contents were analyzed in mung bean extract. Antioxidant activity was evaluated using the DPPH (2,2-diphenyl-1-picrylhydrazyl) radical scavenging assay. Results: Black rice extract exhibited total anthocyanin content of 0.802 ± 0.009 mg/g and total polyphenol content of 7.798 ± 0.178 mg GAE/g. Mung bean extract demonstrated total polyphenol content of 15.113 ± 0.396 mg GAE/g and total flavonoid content of 11.052 ± 0.243 mg QE/g. The DPPH assay revealed IC₅₀ values of 3.252 ± 0.269 ppm for vitamin C, 76.692 ± 2.250 ppm for black rice extract, and 102.130 ± 2.268 ppm for mung bean extract. Conclusion: Black rice extract exhibited superior antioxidant activity compared to mung bean extract, as indicated by its lower IC₅₀ value. Both extracts demonstrated moderate to strong antioxidant potential, suggesting their promising application as natural antioxidant sources for functional food development.